Digital financial inclusion, Financial Mismatch and Small and medium-sized enterprises Financing Constraints - Hu Guohui; Wang Sisi (SHS Web of Conferences, 2023)
Digital financial inclusion through the use of big data, artificial intelligence and other emerging technologies is becoming increasingly sophisticated in China. Using a sample of 843 SMEs in Shenzhen Stock Exchange from 2012-2021, this paper investigates the impact of digital financial inclusion on SMEs’ financing constraints and its mechanism of action using a fixed effects model. It is found that digital financial inclusion can significantly alleviate the financing constraints of SMEs. Further analysis of the mechanism of action reveals that digital financial inclusion can indeed reduce the level of financing constraints by alleviating the financial mismatch of enterprises. The heterogeneity analysis finds that this mitigating effect is greater among non-state versus eastern SMEs. This study sheds new light on alleviating the financing constraints of SMEs and improving financial mismatch.